Green Synthesis of Manganese Dioxide Nanoparticles and its Biological (Baghdad Science Journal, 2024)
The goal of this research is to prepare Manganese dioxide (MnO2) nanoparticles from plant extracts (Puncia granatum L peel, Artemsiai herba-alba Asso, Matricaria chamomilla L, and Camellia sinensis) and test their antibacterial activity. To evaluate the presence of phytochemicals in plant extracts, were used UV-Visible spectrophotometer analysis (UV– Vis), Zeta potential (ZP), and X-ray Diffraction (XRD). The production of MnO2 nanoparticles by plant extracts was shown to have distinctive features. The average crystallite size of manufactured MnO2 NPs was calculated to be between  14.22-21.0 nm, with zeta potential values -23.6, -20.04, -25.6, -16.7  mV, respectively. Manganese dioxide nanoparticles (MnO2 NPs) have significant antibacterial activity against fungi and diverse gram-positive and gram-negative bacteria. The findings results showed that the synthesized MnO2 NPs by P granatum L peel, A herba-alba Asso. plants had the highest percentage of bacterial and fungi inhibition, while M. chamomilla L.and C. sinensis extracts showed lower antifungal activity